Geothermal Energy: Delivering on the Global Potential (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
After decades of being largely the preserve of countries in volcanic regions, the use of geothermal energy-for both heat and power applications-is now expanding worldwide. This reflects its excellent low-carbon credentials and its ability to offer baseload and dispatchable output - rare amongst the mainstream renewables. Yet uptake of geothermal still lags behind that of solar and wind, principally because of (i) uncertainties over resource availability in poorly-explored reservoirs and (ii) the concentration of full-lifetime costs into early-stage capital expenditure (capex). Recent advances in reservoir characterization techniques are beginning to narrow the bounds of exploration uncertainty, both by improving estimates of reservoir geometry and properties, and by providing pre-drilling estimates of temperature at depth. Advances in drilling technologies and management have potential to significantly lower initial capex, while operating expenditure is being further reduced by more effective reservoir management - supported by robust mathematical models - and increasingly efficient energy conversion systems (flash, binary and combined-heat-and-power). Advances in characterization and modelling are also improving management of shallow low-enthalpy resources that can only be exploited using heat-pump technology. Taken together with increased public appreciation of the benefits of geothermal, the technology is finally ready to take its place as a mainstream renewable technology, This book draws together some of the latest developments in concepts and technology that are enabling the growing realisation of the global potential of geothermal energy in all its manifestations.After decades of being largely the preserve of countries in volcanic regions, the use of geothermal energy-for both heat and power applications-is now expanding worldwide. This reflects its excellent low-carbon credentials and its ability to offer baseload and dispatchable output - rare amongst the mainstream renewables. Yet uptake of geothermal still lags behind that of solar and wind, principally because of (i) uncertainties over resource availability in poorly-explored reservoirs and (ii) the concentration of full-lifetime costs into early-stage capital expenditure (capex). Recent advances in reservoir characterization techniques are beginning to narrow the bounds of exploration uncertainty, both by improving estimates of reservoir geometry and properties, and by providing pre-drilling estimates of temperature at depth. Advances in drilling technologies and management have potential to significantly lower initial capex, while operating expenditure is being further reduced by more effective reservoir management - supported by robust mathematical models - and increasingly efficient energy conversion systems (flash, binary and combined-heat-and-power). Advances in characterization and modelling are also improving management of shallow low-enthalpy resources that can only be exploited using heat-pump technology. Taken together with increased public appreciation of the benefits of geothermal, the technology is finally ready to take its place as a mainstream renewable technology.